Peningkatan Pengetahuan Siswa SMP Melalui Edukasi Pengolahan Pangan Lokal Sehat di SMP Al Hasanah Bengkulu - Wulandari, Sri; Elvina, Wica; Ningrum, Nurul Fajar Muslimah (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community service activity aims to improve the knowledge and skills of Al Hasanah Bengkulu Middle School students in processing local food into healthy meals. The background of this program is the low understanding of the younger generation regarding the benefits of local food and healthy eating patterns, which results in a tendency to consume less nutritious instant foods. The implementation method includes preparation (coordination, preparation of materials, and preparation of tools/ingredients), implementation (interactive education, counseling, discussion, and practice of making healthy snacks), and evaluation (pre-test and post-test). A total of 20 students participated in this activity, and the evaluation results showed an increase in knowledge on the definition, examples, and composition of local food, as well as the characteristics of healthy food. However, reinforcement of materials related to the characteristics of local food and healthy food is needed. This program has succeeded in fostering nutritional awareness, pride in local products, and skills in processing local food ingredients. This kind of education is expected to be sustainable through extracurricular activities or further collaboration with schools.